Correlation between Intraoperative Imprint Cytology and Histopathological Diagnosis of Sentinel Lymph Nodes in Clinically Node Negative Breast Carcinomas - R Thangam; Venu Anand; T Vincy (GAIMS Journal of Medical Sciences, 2023)
Introduction: Sentinel lymph node imprint cytology is a reliable method of assessment of axillary lymph node status in clinically node-negative breast cancers. This technique is advantageous in resource-poor settings where cryostats are not available. The results are obtained in a short time, and hence they can be used intra operatively to arrive at a conclusive evidence of metastatic disease in axillary lymph nodes, thereby guiding further treatment. The objective of this study was to compare imprint cytology and histopathological diagnosis of sentinel lymph node in clinically node-negative breast cancers.